How to build a biomarker: IL-7 and acute exacerbation of IPF - Bourbonnais, J.M.; Samavati, L. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Sarcoidosis has different phenotypic manifestations which may have a diverse effect on functional status and quality of life. There are few studies in sarcoidosis addressing gender disparity and its effect on Health-Related Quality of Life (HRQL) and functional status. Objective:The purpose of this study was to investigate the effects of gender on HRQL and to identify associations between poor HRQL and the results of common clinical tests. Design:We assessed HRQL for 221 patients with sarcoidosis in a prospective, crosssectional study using the Short Form-36 Health Survey and Sarcoidosis Health Questionnaire.We evaluated the association between the scores of these measures with patient characteristics, pulmonary function test (PFT) and 6-minute walk test (6MWT) data. Results:Women had lower scores than men on every measure of HRQL and weaker associations to findings from PFT and 6MWT. Multivariate linear regression analyses demonstrated that reduced 6MWT distance and DLCO were significantly associated with poor HRQL in both genders but the sensation of dyspnea played a significant role in women only. Conclusions: Our results indicate that women with sarcoidosis have a lower HRQL score and a greater degree of functional impairment than men. The factors that are associated with poor HRQL differ by gender. Predictors of poor HRQL include reduction in DLCO and 6MWT distance and an increased sensation of dyspnea.